The Effectiveness of Arabic Contextual Teaching and Learning (CTL) Strategy/ Efektifitas Strategy Contextual Teaching and Learning (CTL) Bahasa Arab - Mira Zulistia (UIN ANTASARI, 2021)
This study aims to determine the process of using the CTL (contextual teaching and learning) strategy in learning Arabic speaking skills at MA Manbaul Ulum, and to determine the effectiveness of learning Arabic using the CTL strategy in improving speaking skills at MA Manbaul Ulum. From the research results, it was found that there was a comparison between the pretest experimental class and the control class, in the test (t) the sig value of 0.183 was greater than 0.05 (0.183> 0.05). So there is no difference in ability between the experimental class and the control class before using CTL or the initial ability of the experimental and control class is the same. Then the results of the comparison between the experimental and control class posttest, in the test (t) the sig 0.011 value is smaller than 0.05 (0.011 <0.05). So there is a difference in the results of the study between the experimental class that uses CTL and the control class that does not use CTL to improve speaking skills at MA Manbaul Ulum. It can be concluded that the use of the CTL strategy to improve kalam skills at MA Manbaul Ulum is said to be effective.